O conflito no ensino clínico: uma leitura da teoria do reconhecimento de Axel Honneth - Medeiros, Paulo Vinícius Vasconcelos de (2017)
The Conflict is a central theme for the academic discussions around the Course of Law and its fundamental guidelines of validity. Although conflict is central to addressing law in its most multifaceted spheres, the academy tendsto shy away from addressing the issue by taking into account extraneous and financial and market issues for such oblivion. Honneth's Theory of Recognition assists in confronting this issue with a bias that does not only insert it in its negative or repulsive aspect,but above all in its critical perspective and intersubjectivity, which better guides the subject to autonomy and equality of conditions Of his freedom. The research in question is motivated by the fact that the academic banks of the Law Courses in Brazil do not treat the conflict subjectively or constructively. This is due to the fact that Law courses are often held hostage by external influences which make it a kind of springboard for the labor market and for the approval of students in public examinations and ENADE tests - National Exam Of Performance of Students and of the OAB - Brazilian Bar Association. In the present dissertation it will be treated, based on a bibliographical research, of the existence of the conflict, of how it is seen in the legal science and of the ways of "overcoming it", besides mentioning the birth of the Law itself And how Legal Education is far from such a topic. In order to account for this purpose, we will explore, after presenting a conceptual history of the conflict theme and Honneth's theory of recognition, the ambiguities of the Curricular Guidelines of the Course of Law and Absence of Legal Educationbased on a Theory of Recognition From this step It is intended to point out, on the basis of Honneth's theory of recognition, that this central theme of the spectrum of juridical science could be contemplated in legal education through the view of the theory of Honnethian recognition.